Case Report: Narrative therapy combined with Satir model for the treatment of trichotillomania - Liu, Haiyan; Chen, Xiuxiu; Wan, Xiaochao; Wang, Dan; Chen, Zhiguo (Frontiers in Psychiatry, 2025)
BackgroundTrichotillomania is a chronic psychiatric and behavioral disorder characterized by recurrent hair-pulling, often leading to significant distress and impairment. Long-term psychotherapeutic case reports remain scarce, especially those integrating Narrative Therapy and the Satir Model in culturally-specific and resource-limited contexts.Case PresentationWe present a two-year integrated psychotherapy case for a 28-year-old woman with trichotillomania, utilizing Narrative Therapy and Satir Transformational Systemic Therapy. Assessments included the Massachusetts General Hospital Hair Pulling Scale (MGH-HPS), Self-Rating Anxiety Scale (SAS), Personal and Social Performance Scale (PSP), and Clinical Global Impression (CGI). Hair-pulling episodes decreased from 150 per day to 5, and MGH-HPS, SAS, and PSP scores improved substantially from baseline to end of treatment and one-year follow-up. The patient maintained gains post-treatment, with improved self-worth and social functioning.ConclusionsThis case supports the clinical utility of a Narrative Therapy–Satir Model integration for trichotillomania. The flexible, person-centered approach yielded lasting symptom and functional gains. Limitations include reliance on self-report and potential bias.